Effects of early feed restriction on the performance of broilers - A. H., Ramlah; Halim, A. S.; A. R., Siti Sara (Asian-Australasian Association of Animal Production Societies, 1996)
An experiment was conducted to compare the effects of early feed restriction on the performace and abdominal fat deposition in broilers. The treatments consisted of providing feed ad libitum (Full-fed) and three feed restriction treatments of restricting feeding between 8-21 days of age (DOA) either for a duration of 7 days or 14 days. The three feed restriction treatments were Restrict 8-14 DOA, Restrict 8-21 DOA and Restrict 15-21 DOA. Liveweights and feed consumption were obtained at weekly intervals. Samples of both male and female broilers broilers were taken at 43 DOA to determine the weight of abdominal fat, liver and gizzards. Feed efficiency was generally improved by feed restriction, but a compensatory gain was not observed in the restricted groups. Broilers on restricted feeding also had lower mortality as compared to the full-fed broilers. There is no effect of early feed restriction on the weight of the abdominal fat and the dressing percentages but the weights of the liver and gizzard were affected by restriction. Also there was an effect of sex on the weights of the abdominal fat, the liver and gizzard of the males and females.